Professional preparation for students in the Department of Library and Information Requirements) Department of Libraries at the University of Tishreen model) - Muhanna, Abdul Majid; Ismail, Mays (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed to find out the status quo of the Department of Library and Information at the University of Tishreen stop on what is required and recommended in terms of studies and plans, training programs and projects that make a graduate student of this section Specialist well able to cope and adapt to evolution in which we live now. The researcher used in this research descriptive and analytical approach and style of the case study, as questionnaire was used as a research tool was a random sample of 220 individuals to withdraw, and the participants of the selected sample rate of up to 173 persons or by 78.6%, and its findings the study said most of the respondents increased by 87.9% assert that the courses in the department are not linked to the needs of the labor market, and the results showed that personal desire to enter this specialization increase of 9.8% from the research sample because of the ignorance of many far Library and information Department The importance of this specialization.